A Study on Aflatoxins: Disease and Chemical Prevention - Sood*, Manjulata (Journal of Ecobiotechnology, 2011)
Aflatoxin constitutes a unique group of highly oxygenated coumarin derivative hetrocyclic compound produced by the toxigenic strains of Aspergillus sp.; especially A. flavus Link and A. parasiticus. In biological activities, the toxicity of aflatoxins varies according to the target host, doses and duration of exposure, LD50 is observed in various animals resulted serious problems including carcinoma. U.V. radiation treatment, acetic acid and ammonia etc. are used for prevention of mold growth.